Adoptive Transfer of Regulatory Immune Cells in Organ Transplantation - Oberholtzer, Nathaniel; Atkinson, Carl; Nadig, Satish N. (Frontiers in Immunology, 2021)
Chronic graft rejection remains a significant barrier to solid organ transplantation as a treatment for end-organ failure. Patients receiving organ transplants typically require systemic immunosuppressive in the form of pharmacological immunosuppressants for the duration of their lives, leaving these patients vulnerable to opportunistic infections, malignancies, and other use-restricting side-effects. In recent years, a substantial amount of research has focused on the use of cell-based therapies for the induction of graft tolerance. Inducing or adoptively transferring regulatory cell types, including regulatory T cells, myeloid-derived suppressor cells, and IL-10 secreting B cells, has the potential to produce graft-specific tolerance in transplant recipients. Significant progress has been made in the optimization of these cell-based therapeutic strategies as our understanding of their underlying mechanisms increases and new immunoengineering technologies become more widely available. Still, many questions remain to be answered regarding optimal cell types to use, appropriate dosage and timing, and adjuvant therapies. In this review, we summarize what is known about the cellular mechanisms that underly the current cell-based therapies being developed for the prevention of allograft rejection, the different strategies being explored to optimize these therapies, and all of the completed and ongoing clinical trials involving these therapies.